Shakespeare and the energies of drama - Goldman, Michael, 1936- (Princeton legacy library., 1972)
Shakespeare's texts are seen by the poet and critic Michael Goldman as designs for theatrical experience-the complex emotional, physical, and intellectual transaction between actor and audience that brings alive Shakespeare's imagination and makes it immediate to our own. Mr. Goldman's particular concerns are these: what the audience responds to in an acted play; how Shakespeare controls and shapes this response; what the response means, and why it matters.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.